Hypnic Headache and Basilar Artery Dolichoectasia. Issue 6 (December 2015) - Moreira, Isabel; Mendonça, Teresa; Monteiro, José P.; Santos, Ernestina
Abstract : Background: Hypnic headache is regarded by most authors as a primary headache, but in some cases it was considered secondary to hypophysis, brain stem, or posterior fossa lesions. Case: We report a case of a 69-year-old woman with a history of a headache that fulfils all International Classification of Headache Disorders-II criteria for hypnic headache, with 2 years of evolution, whose complementary investigation with magnetic resonance and magnetic resonance angiography revealed a dolichoectasia of the basilary artery. She was treated with verapamil with excellent response. Conclusions: To the best of our knowledge, this is the first described case of a patient with hypnic headache and a dolichoectasic basilar artery. The relation between these 2 entities is questionable, but we raise some possible explanations for this relationship.